2015
DOI: 10.1126/scitranslmed.aaa4691
|View full text |Cite
|
Sign up to set email alerts
|

Improved antitumor activity of immunotherapy with BRAF and MEK inhibitors in BRAF V600E melanoma

Abstract: Combining immunotherapy and BRAF targeted therapy may result in improved antitumor activity with the high response rates of targeted therapy and the durability of responses with immunotherapy. However, the first clinical trial testing the combination of the BRAF inhibitor vemurafenib and the CTLA-4 antibody ipilimumab was terminated early due to substantial liver toxicities. MEK inhibitors can potentiate the MAPK inhibition in BRAF mutant cells, while potentially alleviating the unwanted paradoxical MAPK activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
333
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(367 citation statements)
references
References 44 publications
12
333
2
5
Order By: Relevance
“…In fact, concurrent administration of BRAF and MEK inhibitors with ACT resulted in dramatic tumor response, increased T-cell infiltration, and effector functions in a syngeneic immunocompetent melanoma mouse model [114]. This was accompanied by increase in melanoma-associated antigens [114].…”
Section: Double Mapk Blockade Through Braf and Mek Inhibition In Combmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, concurrent administration of BRAF and MEK inhibitors with ACT resulted in dramatic tumor response, increased T-cell infiltration, and effector functions in a syngeneic immunocompetent melanoma mouse model [114]. This was accompanied by increase in melanoma-associated antigens [114].…”
Section: Double Mapk Blockade Through Braf and Mek Inhibition In Combmentioning
confidence: 99%
“…In fact, concurrent administration of BRAF and MEK inhibitors with ACT resulted in dramatic tumor response, increased T-cell infiltration, and effector functions in a syngeneic immunocompetent melanoma mouse model [114]. This was accompanied by increase in melanoma-associated antigens [114]. However, MEK inhibition was able to overcome the increase in intratumoral T-regulatory cells and macrophages observed after treatment with BRAF and ACT [114].…”
Section: Double Mapk Blockade Through Braf and Mek Inhibition In Combmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, antibody-mediated blockade of CTLA-4 induces complete tumor rejection and immunologic memory in several murine models of cancer (14). In addition, preclinical murine studies have shown that CTLA-4 blockade synergizes with radiation therapy (15), chemotherapy (16), molecularly targeted therapy (17), and tumor vaccination (18) to eradicate established tumors. Mechanistic studies in mice have shown that CTLA-4 blockade increases the ratio of effector T-cells to Foxp3+ Treg cells in tumors (19).…”
Section: Ctla-4 In Cancermentioning
confidence: 99%
“…The combination of targeted therapy with BRAF and MEK inhibitors has become the standard of care in patients with BRAF (V600E) mutant melanoma and can be used in about one half of patients but they mostly develop resistance a few months after initiation [3,4,5]. Approximately 19-58% of patients with metastasis of melanoma benefit from a systemic immunotherapy, depending on mono- or combination therapy [6,7].…”
Section: Introductionmentioning
confidence: 99%